2016
DOI: 10.1136/jclinpath-2016-204044
|View full text |Cite
|
Sign up to set email alerts
|

HPV self-sampling in CIN2+ detection: sensitivity and specificity of different RLU cut-off of HC2 in specimens from 786 women

Abstract: Our results confirm that the cut-off value of 1 suggested by Qiagen for PreservCyt specimen is the best cut-off value also for self-sampled specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…10 This is also in accordance with several previous studies, where women with lower viral load was mostly found with NILM as result of cytology test and had lower chance for developing CIN2+, contrary with women with a raised viral load who were mostly found with abnormal cytology results, and had a greater chance of developing CIN2+ lesions or more. 7,8,11 Furthermore, in this study, prevalence of CIN2-3 grade lesions was markedly found in women with higher HPV viral load, comparing to those with a lower viral load who were mostly found with normal results or low-grade lesions. High frequency of biopsy-confirmed CIN2-3 was considerably related to elevated viral load detected by the HC2 assay.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…10 This is also in accordance with several previous studies, where women with lower viral load was mostly found with NILM as result of cytology test and had lower chance for developing CIN2+, contrary with women with a raised viral load who were mostly found with abnormal cytology results, and had a greater chance of developing CIN2+ lesions or more. 7,8,11 Furthermore, in this study, prevalence of CIN2-3 grade lesions was markedly found in women with higher HPV viral load, comparing to those with a lower viral load who were mostly found with normal results or low-grade lesions. High frequency of biopsy-confirmed CIN2-3 was considerably related to elevated viral load detected by the HC2 assay.…”
Section: Discussionsupporting
confidence: 50%
“…Borrai F et al, has shown that 5 to 15% of women who underwent treatment for CIN2+ will redevelop the disease within 2 years postoperative. 11 According to Jeong NH, 5 to 25% of them will have recurrent disease. 18 In a recent study, rate of persistence of high grade CIN after treatment was 25.7% and it has been shown to be mostly associated with persistent HPV 16 infection.…”
Section: Discussionmentioning
confidence: 99%